Peran Pengetahun terhadap Sikap kepada Pasien Epilepsi pada Mahasiswa dan Staf Universitas Dian Nuswantoro - Tiara Fani (VISIKES: Jurnal Kesehatan Masyarakat, 2017)
More than half of 50 million worldwide epilepsy patients expected to live in Asia. Public knowledge and attitudes toward epilepsy patients need to be known to prevent social discrimination. Cross-Sectional study was conducted on 223 samples (lecturers, staff and students) at Dian Nuswantoro University. Data collection used questionnaire. The results showed that, 184 respondents(82.5%) had information about epilepsy, 91 respondents (40.8%) knew the cause of epilepsy, and 164 respondents (73.5%) knew that epilepsy was not contagious. While attitudes toward epilepsy patients, 137 respondents (61.4%) are willing to help, 8 respondents (3.6%) will stay away when seeing epilepsy patients experience a seizure attack. Knowledge about epilepsy affect attitudes toward epilepsy patients (p = 0.003; r = 0.182). Ignorance about the transmission of epilepsy (p = 0,007, r = -0,180) and understanding that epilepsy is a curable disease (p = 0,031, r = -0,145) have more influence on low willingness to give help epilepsy patients when they experience seizure attack. In-depth interviews need to be done on future research to gain a deeper information about public’s attitude toward epilepsy patients.Keywords: epilepsy, knowledge, attitude